2017
DOI: 10.1063/1.4999192
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cs2AgSbCl6 and improved optoelectronic properties of Cs2AgSbCl6/TiO2 heterostructure driven by the interface effect for lead-free double perovskites solar cells

Abstract: Double perovskites Cs2AgSbCl6 have been synthesized via the solution state for applications as a promising photovoltaic absorber. Considering TiO2 as an electron transport layer (ETL), Cs2AgSbCl6/TiO2 heterojunction nanoparticles have also been prepared by the hydrothermal process to study the interface effect. Experimental measurements show that Cs2AgSbCl6 has a cubic structure with the lattice constant of 10.699 Å. The absorption peaks in the optical spectrum of the Ag and Sb-based double perovskites agree w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 39 publications
5
51
0
Order By: Relevance
“…Cs 2 AgSbCl 6 has a cubic structure with Fm‐3m space group symmetry and investigational unit‐cell axis parameters a = b = c =10.699 Å, and its optical bandgap is around 2.60 eV . The interplanar spacing values between (200) and (220) planes of Cs 2 AgSbCl 6 were demonstrated to be 2.6 and 1.8 Å, respectively .…”
Section: Materials and Structuresmentioning
confidence: 98%
See 2 more Smart Citations
“…Cs 2 AgSbCl 6 has a cubic structure with Fm‐3m space group symmetry and investigational unit‐cell axis parameters a = b = c =10.699 Å, and its optical bandgap is around 2.60 eV . The interplanar spacing values between (200) and (220) planes of Cs 2 AgSbCl 6 were demonstrated to be 2.6 and 1.8 Å, respectively .…”
Section: Materials and Structuresmentioning
confidence: 98%
“…Note that the optical absorption of Cs 2 AgSbCl 6 could be tunable by means of heterostructure engineering combined with other wide‐bandgap semiconductors. For example, the Cs 2 AgSbCl 6 /TiO 2 heterostructure displays improved optical absorption ability in the visible‐light region in composition to that of the pure Cs 2 AgSbCl 6 perovskite, which is associated with the formation of the declined bandgap and the interfacial states, thereafter facilitating the photoinduced optical transition upon the visible‐light illumination …”
Section: Materials and Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…First, among the 8 B(I) cations, the 5 alkali metal cations (including NH 4 + ) can be directly ruled out because they are too ionic to contribute to the band edges. [166] Since 2016, many new halide double perovskites have been synthesized, including Cs 2 AgBiX 6 (X = Br, Cl), [155][156][157] Cs 2 AgSbCl 6 , [167][168][169] Cs 2 AgInCl 6 , (MA) 2 AgBiBr 6 , [170] (MA) 2 KBiCl 6 , [161] and (MA) 2 TlBiBr 6 . [55] Second, for B(III) cations, the transition metal cations with multiple oxidation states and/or partially occupied d or f orbitals are not desirable for designing photovoltaic absorbers, because they may introduce deep defect states and too localized band edges.…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
“…According to the results, we concluded that double perovskites could been synthesized when ∆H d is greater than 0 meV per atom, [32,37,40,[52][53][54][55][56][57][58][59] and there is no synthesis in the experiment when ∆H d is lower than −29 meV per atom. It is worth noting that ∆H d is between −29-0 meV per atom, that is, Cs 2 AgSbCl 6 [44,60], Rb 2 NaInCl 6 [53], Cs 2 AgSbBr 6 [44], Cs 2 NaInBr 6 [53], Cs 2 KBiCl 6 [61], Cs 2 NaSbBr 6 [54], Cs 2 NaBiI 6 [43] and Cs 2 AgBiI 6 [62] are experimentally synthesized by synthesizing nanocrystals or controlling the experimental temperature. We listed the bandgap, decomposition energies and optimal decomposition pathways in Table S3.…”
Section: Linear Programming (Lp) For Thermodynamic Stabilitymentioning
confidence: 99%